2021
DOI: 10.33545/gynae.2021.v5.i2d.889
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and practices regarding menstrual cup among reproductive women in a rural tertiary care Hospital

Abstract: Background:The menstrual cup is a recently developed alternative to sanitary napkins. Hence, in this present study, the knowledge, practices, and attitudes of menstrual cups among rural adult women were evaluated. Methods: This cross-sectional study was conducted on women who are in the age group of 18-45 years and are willing to participate in the study. The relevant data were collected using a preformed questionnaire. The questionnaire included all the data about the demographic parameters including age, edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 10 publications
0
0
0
Order By: Relevance
“…In the present study, the main concern about the use of menstrual cup was discomfort (54.2%) followed by leakage (18%). Whereas a similar study done by Meghana et al [9] reported leakage as main concern followed by discomfort. Also a meta analysis done by Anna et al [10] with regard to availability use and safety of menstrual cup he concluded that outcome of leakage and reported leakage was similar or lower for menstrual cups than for disposable pads or tampons.…”
Section: Discussionmentioning
confidence: 75%
“…In the present study, the main concern about the use of menstrual cup was discomfort (54.2%) followed by leakage (18%). Whereas a similar study done by Meghana et al [9] reported leakage as main concern followed by discomfort. Also a meta analysis done by Anna et al [10] with regard to availability use and safety of menstrual cup he concluded that outcome of leakage and reported leakage was similar or lower for menstrual cups than for disposable pads or tampons.…”
Section: Discussionmentioning
confidence: 75%
“…The studies conducted in different parts of India find a massive gap between the knowledge and willingness of women to accept the menstrual cup. (4,8) In a study conducted by Swetha and Amritha, The study participants were mainly medical and paramedical students (16-30 years of age) in south India; it was reported that though 82% of the participants have good knowledge about the menstrual cup among them, 65.75% have knowledge about menstrual cup usage, but only 6% had used MC. (13) Studies also found menstrual cups pose no health hazards to women.…”
Section: Menstrual Cup Use In the Indian Contextmentioning
confidence: 99%